Analisis Sentimen Masyarakat Terhadap Isu Migrasi Rohingya Ke Indonesia - Kurniasih, Ulfa; Suseno, Akrim Teguh (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
The phenomenon of the Rohingya refugee exodus is something that attracts a lot of public interest on social media. This study aims to see how the public represents the phenomenon of the presence of Rohingya refugees in Indonesia on X social media with the Decision tree 5.0 algorithm and Naive bayes with the keyword